Growing of motor-car tires shallow with the use of knives of fixed by the evtectic powder-like electrodes of the system Fe-Mn-C-B - Пашечко, М.І.; Домбскі, Я. (Problems of Tribology, 2014)
The technological line of growing of motor-car tires with the use of knives of fixed shallow is described by the evtectic powder-like electrodes of the system Fe-Mn-C-B. It is shown, that the greatest wearproof of knives is got at the use the vanadium and chrome electrodes of firm Lastec.